STUDY OF CARDIOPROTECTIVE ACTIVITY OF NORMOVEDIC IN CCL4 INDUCED CARDIOTOXICITY IN RATS - UTTAM PAUL; SHIVALINGE GOWDA KP (International Journal of Pharma and Bio Sciences, 2016)
The cardioprotective activity of Normovedic was investigated using carbon tetrachloride (CCl4) induced cardiotoxicity. The rats were divided into 5 groups (n=6). Group I was considered normal. The Normovedic was administered orally at a dose of 39 mg/kg p.o for 8 weeks to the group II, IV. Silymarin (100mg/kg) was used as a standard cardioprotective drug and was administered for 8 weeks to the group V. The CCl4 1 ml/kg with liquid paraffin (1:1 ratio) i.p twice a week for 4 weeks (5th to 8th week) to the group III,IV and V. After 24h of the last treatment ECG was measured under ketamine and xylazine anesthesia (65, 9mg/kg bw ip) in all the rats. Then the rats were sacrificed by overdose ketamine anesthesia (150mg/kg ip). The blood was withdrawn by retro orbital puncture and processed to serum. The heart was isolated and heart PMS was prepared. The serum biomarkers CK-MB, CK, LDH and cardiac tissue SOD were determined. The CK-MB, CK, LDH levels were significantly decreased, whereas SOD levels were significantly increased in Normovedic treated rats when compared to CCl4 toxic control rats (group III). The CCl4 administered rats (Group III) showed alterations in ECG and heart weight, histological examination when compared to normal rats these alterations were significantly recovered in the Group IV & Group V treated rats. From the results of this study it is concluded that the Normovedic (a poly herbal formulation) possesses cardioprotective properties which may help to protect users against complications due to cardiotoxicity.